O consumo de experiências felizes na #tbt no instagram - Pacheco, Paula Lopes Zoza Guiro (2023)
This research addresses the theme of happiness consumption on Instagram, focusing on the Throwback Thursday movement, or #tbt. Instagram, created in 2010, derives its name from the combination of "instant camera" and "telegram," referring to the immediacy in sharing moments experienced by users. Today, it ranks among the top five most used social networks globally. #tbt is one of the most used hashtags on social media, allowing users to bring back photos from the past to keep their feed updated, also working on the user's emory. Few previous studies have been found regarding the theme associated with the #tbt hashtag, which prompted the research aiming to understand how #tbt operates in the consumption of happy experiences on Instagram and its possible implications in other forms of consumption, such as acquisitions and appropriations of products and services. The Uses and Gratifications Theory lenses were used to construct the object. The study is exploratory in nature, employing a qualitative approach to seek interpretations that enable the achievement of the research objectives. It was identified that #tbt is a tool that assists in maintaining a happy feed, and both Instagram and #tbt are part of cycles involving the production, dissemination, and visualization/evaluation of memories constructed through the editing and/or curation of ordinary and extraordinary moments lived by people and considered happy.